Digitalization of Bookkeeping and Strengthening Financial Management Competencies for MSME Actors - Bella Suci Novitri; Walla Astianty Putri; Joko Rianto; Muhammad Fikri (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid advancement of digital technology has transformed financial management practices across business sectors, including Micro, Small, and Medium Enterprises (MSMEs). Nevertheless, many MSME actors continue to encounter challenges in maintaining systematic financial records and developing adequate financial management competencies due to limited accounting knowledge, low digital literacy, and the continued use of manual bookkeeping practices. This study aims to explore how the digitalization of bookkeeping contributes to strengthening the financial management competencies of MSME actors and to identify the opportunities and challenges associated with its implementation. A qualitative research design employing a descriptive case study approach was adopted. Data were collected through in-depth interviews, participant observations, and document analysis involving MSME owners, business mentors, and representatives from relevant government agencies. The data were analyzed using thematic analysis through the processes of data reduction, data display, and conclusion drawing, while data credibility was ensured through source triangulation, member checking, and peer debriefing. The findings reveal that bookkeeping digitalization significantly enhances the financial management competencies of MSME actors by improving the accuracy of financial recording, facilitating real-time financial monitoring, strengthening budgeting and cash flow management, and supporting evidence-based business decision-making. Furthermore, digital bookkeeping promotes greater financial discipline, accountability, and transparency, enabling MSMEs to improve business sustainability and expand access to external financing. However, successful implementation remains constrained by disparities in digital literacy, technological infrastructure, financial resources, and continuous technical assistance. This study contributes to the growing literature on digital transformation and MSME financial capability by providing an in-depth understanding of the mechanisms through which digital bookkeeping fosters financial competency development. The findings offer practical implications for policymakers, financial institutions, and MSME development agencies in designing inclusive digital financial literacy programs and sustainable capacity-building initiatives that accelerate MSME digital transformation.